PINK1 modulates Prdx2 to reduce lipotoxicity‐induced apoptosis and attenuate cardiac dysfunction in heart failure mice with a preserved ejection fraction - Hao Zhang; Tianyu Xu; Xiyuan Mei; Qiming Zhao; Qiling Yang; Xianghui Zeng; Zhuang Ma; Haobin Zhou; Qingchun Zeng; Dingli Xu; Hao Ren (Clinical and Translational Medicine, 2025)
Abstract Introduction Heart failure with preserved ejection fraction (HFpEF) is a complex condition characterized by metabolic dysfunction and myocardial lipotoxicity. The roles of PTEN‐induced kinase 1 (PINK1) and peroxiredoxin‐2 (Prdx2) in HFpEF pathogenesis remain unclear. Objective This study aimed to investigate the interaction between PINK1 and Prdx2 to mitigate cardiac diastolic dysfunction in HFpEF. Methods In vivo, PINK1‐knockout mice and cardiac‐specific PINK1‐overexpressing transgenic mice were used to establish an HFpEF mouse model via a high‐fat diet and L‐NAME. Myocardial lipotoxicity was induced by palmitic acid in vitro. Immunoprecipitation, western blotting and immunofluorescence analysis were performed to elucidate the molecular mechanisms involved. Results We determined that PINK1 and Prdx2 were downregulated in the HFpEF mouse model. In vivo, PINK1 ablation exacerbated the reduction in Prdx2 expression, worsening cardiac dysfunction in HFpEF mice. Conversely, PINK1 overexpression restored Prdx2 levels and decreased reactive oxygen species and apoptosis, thereby reducing fibrosis and inflammation and ameliorating cardiac diastolic dysfunction in HFpEF mice. In vitro, an interaction between the N‐terminal region (amino acids 1–133) of PINK1 and Prdx2 was identified. The overexpression of PINK1 induced Prdx2 expression and effectively attenuated palmitic acid‐induced apoptosis through the c‐Jun amino‐terminal kinase (JNK) and mitogen‐activated protein kinase (p38) pathways, whereas siRNA‐mediated Prdx2 knockdown abolished the protective effect of PINK1. Conclusion PINK1 alleviates lipotoxicity‐induced myocardial apoptosis and improves diastolic dysfunction in HFpEF through Prdx2, highlighting PINK1 overexpression as a potential therapeutic strategy for HFpEF. Key points Our investigation discloses a pivotal relationship between PINK1 and Prdx2 in the context of HFpEF. Notably, PINK1, in addition to its role in mitochondrial autophagy, can increase Prdx2 expression, effectively remove ROS and attenuate cardiomyocyte apoptosis by modulating the JNK and p38 pathways, thereby alleviating myocardial lipotoxicity and improving HFpEF cardiac function. Our studies offer valuable insights, opening avenues for the development of innovative therapeutic strategies in the prevention and treatment of HFpEF.